#MindinBody - feasibility of vigorous exercise (Bikram yoga versus high intensity interval training) to improve persistent pain in women with a history of trauma: a pilot randomized control trial - Alison Flehr (BMC Complementary and Alternative Medicine, 2019)
Abstract Background The neurobiology of persistent pain shares common underlying psychobiology with that of traumatic stress. Modern treatments for traumatic stress often involve bottom-up sensorimotor retraining/exposure therapies, where breath, movement, balance and mindfulness, are used to target underlying psychobiology. Vigorous exercise, in particular Bikram yoga, combines many of these sensorimotor/exposure therapeutic features. However, there is very little research investigating the feasibility and efficacy of such treatments for targeting the underlying psychobiology of persistent pain. Methods This study was a randomized controlled trail (RCT) comparing the efficacy of Bikram yoga versus high intensity interval training (HIIT), for improving persistent pain in women aged 20 to 50 years. The participants were 1:1 randomized to attend their assigned intervention, 3 times per week, for 8 weeks. The primary outcome measure was the Brief Pain Inventory (BPI) and further pain related biopsychosocial secondary outcomes, including SF-36 Medical Outcomes and heart rate variability (HRV), were also explored. Data was collected pre (t0) and post (t1) intervention via an online questionnaire and physiological testing. Results A total of 34 women were recruited from the community. Analyses using ANCOVA demonstrated no significant difference in BPI (severity plus interference) scores between the Bikram yoga (n = 17) and the HIIT (n = 15). Women in the Bikram yoga group demonstrated significantly improved SF-36 subscale physical functioning: [ANCOVA: F(1, 29) = 6.17, p = .019, partial eta-squared effect size (ηp 2) = .175 and mental health: F(1, 29) = 9.09, p = .005, ηp 2 = .239; and increased heart rate variability (SDNN): F(1, 29) = 5.12, p = .013, ηp 2 = .150, scores compared to the HIIT group. Across both groups, pain was shown to decrease, no injuries were experienced and retention rates were 94% for Bikram yoga and 75% for HIIT . Conclusions Bikram yoga does not appear a superior exercise compared to HIIT for persistent pain. However, imporvements in quality of life measures and indicator of better health were seen in the Bikram yoga group. The outcomes of the present study suggest vigorous exercise interventions in persistent pain cohorts are feasible. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12617001507370, 26/10/2017).